Analisis Loyalitas Pelanggan Sebagai Kunci Sukses Pemasaran Studi Kasus Pada Produk Kosmetik Wardah - Defi herfiana; Arfiani Yulianti Fiyul (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze how customer loyalty plays a strategic role in the marketing success of Wardah cosmetic products amidst the increasingly competitive halal cosmetics industry. The study used a qualitative approach with a case study to understand the experiences, perceptions, and meaning of customer loyalty from the perspectives of consumers and the company. Data collection was conducted through in-depth interviews, observations of digital marketing activities, and documentation studies, with informants selected purposively and developed using a snowball sampling technique. Data analysis was conducted interactively through a continuous process of data reduction, data presentation, and conclusion drawing. The results show that Wardah customer loyalty is formed through a positive interaction between safe and Sharia-compliant product quality, a strong halal brand image, and a digital marketing strategy that builds emotional attachment and long-term trust. Loyalty is defined not only as repeat purchases but also as an emotional commitment that encourages voluntary recommendations and resilience to the influence of competing brands. In conclusion, Wardah has successfully utilized customer loyalty as an effective marketing strategy through strengthening its halal image, continuous product innovation, and digital-based customer experience management, thereby retaining customers and maintaining competitiveness in the halal cosmetics industry.